Monetary policy delegation, labour market structure and fiscal-monetary policy coordination - Olli Castrén (Bank of Finland, 1998)
We study monetary policy delegation in a framework where fiscal policy is determined endogenously and wages are negotiated by trade unions who face a trade-off between real wages and employment.If the median trade union voter is a senior member the nominal wages are too high to guarantee full insider. employment.The fiscal authority can subject the central bank to institutional arrangements.The optimal choice of central bank preferences shows a central banker who is more inflation averse, but not infinitely so, than the fiscal authority.This happens because employment and government expenditures are not invariant to changes in the monetary regime.If the fiscal authority gives the central bank to an inflation target, the optimal target is contingent upon both the fiscal authority's and the trade union's preferences.Moreover, the fiscal authority's gain from inflation targeting is highest if the median union voter has no employment objective.When the union cares about employment, both fiscal and monetary policies become subject to time-inconsistency problems.In equilibrium, the overall welfare under inflation targeting can be lower than under discretion.However, when the union's employment objective becomes sufficiently important, the gain starts to increase.Thus, we find a U-shaped relationship between the gain from inflation targeting and the trade union's weight on employment.
URN:NBN:fi:bof-20140807468
Keywords: 330; Trade Union Behaviour; Fiscal-Monetary Coordination; Inflation Targeting